Technology-assisted cognitive-behavior therapy delivered by peers versus standard cognitive behavior therapy delivered by community health workers for perinatal depression: study protocol of a cluster randomized controlled non-inferiority trial - Atif Rahman; Abid Malik; Najia Atif; Huma Nazir; Ahmed Zaidi; Anum Nisar; Ahmed Waqas; Maria Sharif; Tao Chen; Duolao Wang; Siham Sikander (Trials, 2023)
Abstract Background The lack of trained mental health professionals is a key barrier to scale-up of evidence-based psychological interventions in low and middle-income countries. We have developed an app that allows a peer with no prior experience of health-care delivery to deliver the cognitive therapy-based intervention for perinatal depression, the Thinking Healthy Programme (THP). This trial aims to assess the effectiveness and cost-effectiveness of this Technology-assisted peer-delivered THP versus standard face-to-face Thinking Healthy Programme delivered by trained health workers. Methods We will employ a non-inferiority stratified cluster randomized controlled trial design comparing the two formats of intervention delivery. A total of 980 women in the second or third trimester of pregnancy with a diagnosis of Major Depressive Episode, evaluated with the Structured Clinical Interview for DSM-V Disorders (SCID), will be recruited into the trial. The unit of randomization will be 70 village clusters randomly allocated in a 1:1 ratio to the intervention and control arms. The primary outcome is defined as remission from major depressive episode at 3 months postnatal measured with the SCID. Data will also be collected on symptoms of anxiety, disability, quality of life, service use and costs, and infant-related outcomes such as exclusive breastfeeding and immunization rates. Data will be collected on the primary outcome and selected secondary outcomes (depression and anxiety scores, exclusive breastfeeding) at 6 months postnatal to evaluate if the improvements are sustained in the longer-term. We are especially interested in sustained improvement (recovery) from major depressive episode. Discussion This trial will evaluate the effectiveness and cost-effectiveness of a technology-assisted peer-delivered cognitive behavioral therapy-based intervention in rural Pakistan. If shown to be effective, the novel delivery format could play a role in reducing the treatment gap for perinatal depression and other common mental disorders in LMIC. Trial registration The trial was registered at Clinicaltrials.gov (NCT05353491) on 29 April 2022.